Democratic governance and social inequality - Tulchin, Joseph S.; Brown, Amelia (Boulder : L. Rienner Publishers, 2002)
This text examines the challenges that social inequities present to democratic governance. The authors argue that issues of poverty and inequality - far from diminishing - are becoming even more important in the present global environment.
Includes bibliographical references and index.
Keywords: Democracy -- Economic aspects; Economic development -- Political aspects; Democracy -- Case studies; Economic development -- Case studies; Equality; Social justice